School Leadership in a Contradictory World - Moos, Lejf (Revista de Investigación Educativa, 2012)
The article captures important trends and tendencies in public governance and thus in conditions for school leadership. The general movement towards Globalization influences the core trends in national policies and in public governance. But international discourses and practices are formed in national or regional contexts of culture, practice and politics. The author is part of a Nordic context and therefore he observes governance and leadership from this point. But it is possible to translate the analyses to other contexts as well. An analyse of some of the effects of the meetings of transnational influences with national values and practises are discussed in the case of Danish education and school leadership. School leaders are left with a number of dilemmas between traditional, welfare state values and neo-liberal values. They have to find locally satisfying balances between academic proficiencies and competences of curiosity and deliberation.